Reactivity of brain blood flow in patients with Tension-type Headache - Kalashnikov Valeriy Yosypovych; Stoyanov Oleksandr Mykolaiovych (Scientific Research and Experimental Development, 2024)
Tension-type headache is very common, with a lifetime prevalence in the general population ranging in different studies between 30% and 78%. The percentage of the adult population with an active headache disorder is 47% for headache in general, 10% for migraine, 38% for tension-type headache, and 3% for chronic headache that lasts for more than 15 days per month. Primary tension-type headaches occur in approximately 40% of the adult population worldwide. Central sensitization caused by prolonged nociceptive input from muscles is considered to play an important role for chronification of tension-type headache. Directly and indirectly chronic tension-type headache (CTTH) causes high costs and considerable loss of quality of life. The pain rating of the electrical stimuli and the pain score of the hypertonic saline infusion were significantly higher in CTTH patients than in healthy volunteers. The primary endpoint was the relative change of the blink reflex integral immediately after hypertonic saline infusion. It was significantly smaller in CTTH patients on the contralateral side compared to healthy volunteers, while there was no significant difference on the ipsilateral side. Neck pain is highly prevalent in the general population and even more prevalent in individuals with primary headaches. Prevalence is highest in coexistent M+TTH, followed by pure TTH and migraine. Myofascial tenderness is significantly increased in individuals with neck pain. Tension-type headache has a high socio-economic impact. Divided into episodic and chronic types, introduced in the manual "International Classification of Headache Disorders"(ICHD-III), it has practical importance. Infrequent episodic headaches (no more than once a month) may not require drug therapy, but, on the contrary, frequent forms may require expensive treatment. Chronic tension-type headache is a serious disease, causing greatly decreased quality of life and high disability.